Culinary Diplomacy as Cultural Learning: Introducing Indonesian Traditional Snacks to Thai Students at Thammasat University - Nadofah Nadofah; Rosida Rosida; Nadofah Nadofah; Rosida Rosida (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2026)
This international community service activity aimed to introduce Indonesian traditional snacks to Thai students at Thammasat University as a medium for cultural learning and culinary diplomacy. The activity was conducted at the Faculty of Liberal Arts, Thammasat University, Bangkok, Thailand, involving approximately 20 students enrolled in Indonesian language courses. The implementation method adopted an experiential learning approach through interactive presentations, culinary demonstrations, food tasting sessions, and cultural exchange discussions between lecturers and students. Indonesian traditional snacks introduced during the activity included brem, banana sale, rengginang, tempe chips representing the diversity of Indonesian culinary heritage. The results of the activity indicate that participants responded positively and showed increased understanding of Indonesian culinary culture while being able to practice Indonesian vocabulary related to food and taste. The main outcomes of the program include enhanced cross-cultural understanding among students, the creation of two-way cultural interaction between Indonesian facilitators and Thai students, and the strengthening of academic collaboration between Universitas Pembangunan Nasional “Veteran” Jawa Timur and Thammasat University through community service activities based on culinary diplomacy.